(untitled) (The International Journal for Scientific Research, 2026)
The study aimed to uncover the role of governance standards in enhancing organizational trust in the Ministry of Hajj and Umrah. The study followed a descriptive survey methodology, where a questionnaire prepared by the researcher was administered to a representative sample of the study population, consisting of (316) employees of the Ministry of Hajj and Umrah. The study found that the impact of governance standards in the ministry on the level of organizational trust among employees averaged (4.399), indicating a very high degree. And the results also showed that the sample’s estimation of the key factors to be considered to improve organizational trust within the ministry averaged (4.449), which is also very high. Additionally, the sample’s estimation of the level of impact of organizational trust on employee behaviors within the ministry averaged (4.437), again indicating a very high degree. Furthermore, the study indicated that the sample’s estimation of the mechanisms that can be adopted to improve organizational trust and employee performance in line with government requirements averaged (4.462), which is also very high. Based on these results, the study recommends that senior management continuously emphasize the importance of integrity and professional ethics, which are key objectives of Vision (2030), and enhance them through regular training courses and workshops for employees. The study also recommends adopting clear governance policies and procedures and regularly monitoring their implementation to ensure everyone’s compliance with these standards by senior management. Additionally, the study suggests establishing independent committees to monitor and review the application of governance standards periodically and provide transparent reports on the level of compliance, as well as adopting policies that ensure job stability for employees, such as long-term employment contracts and clear promotion policies, to enhance employee confidence and their continued commitment.